Study on Sound Absorption Performance and Transmission Behavior of Perpendicular-laid Nonwovens (Journal of Fiber Bioengineering and Informatics, 2018)
This work deals with the study of acoustic performance of perpendicular-laid nonwovens and their relation to fabric air permeability and thermal properties. Seven perpendicular-laid nonwoven fabrics were selected to examine sound absorption like average values of sound absorption coefficients (\bar{α}) and noise reduction coefficient (NRC) as well as air permeability and thermal insulation properties. The Brüel and Kjær impedance tube instrument, Alambeta and FX3300 Air Permeability Tester were used for evaluation of acoustic, thermal and air permeability properties, respectively. It was observed that sound absorption had insignificant correlation with thermal conductivity while it was strongly correlated with thermal resistance. And the correlation coefficient of NRC and thermal resistance was 0.9835, indicating that NRC was directly proportional to thermal resistance of perpendicular-laid nonwovens. It also was observed that \bar{α} was inversely proportional to air permeability, with correlation coefficient 0.95. It was concluded that a higher thermal resistance and lower air permeability suggested a better sound absorption performance for a perpendicular-laid nonwoven fabric.